Women's participation in the management of Brazilian rural enterprises (Research, Society and Development, 2022)
Approximately 30 million people live in Brazilian rural areas, with very different realities and not always favorable to access to fundamental rights, such as health, leisure, education, security, income, food. So, how could these individuals remain in these territories, reaching the state of human development? And do rural women have the autonomy to develop their life projects, including leading rural enterprises or is it something exclusive to men, especially traditional patriarchal family structures? What would limit them and make it possible to extrapolate the stereotype of a caregiver in going to head the rural properties, including family organizations or not? The present work enables a theoretical review and discussion on the subject and raises opportunities for scientific investigation. It is divided into the debate on women, the world of work, the Brazilian countryside and the management characteristics of its enterprises.